Molecular and clinical profile of VWD in a large cohort of Chinese population: application of next generation sequencing and CNVplex® technique - Liang, Qian; Qin, Huanhuan; Ding, Qiulan; Xie, Xiaoling; Wu, Runhui; Wang, Hongli; Hu, Yiqun; Wang, Xuefeng (Thrombosis and Haemostasis, 2017)
Von Willebrand disease (VWD), the most common inherited bleeding disorder, is characterised by a variable bleeding tendency, heterogeneous laboratory phenotype and race specific distribution of mutations. The present study aimed to determine the correlation of genotype and phenotype in 200 Chinese individuals from 90 unrelated families with VWD. Next generation sequencing (NGS) of the whole coding VWF, copy number analysis of VWF by CNVplex® technique as well as a comprehensive phenotypic assessment were carried out in all index patients (IPs). We identified putative mutations in all IPs except five mild type 1 (85/90, 94.4%). In total, 98 different mutations were detected, 62 (63.3% of which were reported for the first time (23 missense mutations, 1 regulatory mutation, 12 splice site mutations and 26 null mutations). Mutations p.Ser1506Leu and p.Arg1374His/Cys/ Ser were the most frequent mutations in 2A (33% of cases) and 2M VWD (67% of cases), respectively. In addition, mutation p.Arg816Trp was detected repeatedly in type 2N patients, while mutation p.Arg854Gln, extremely common in Caucasians, was not found in our cohort. Thirty-three patients had two or more putative mutations. Unlike most cases of type 1 and type 2 VWD, which were transmitted dominantly, we presented seven severe type 1, two type 2A and one type 2M with autosomal recessive inheritance. Here the phenotypic data of patients with novel mutations will certainly contribute to the better understanding of the molecular genetics of VWF-related phenotypes.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: von Willebrand disease; von Willebrand factor; NGS; genotype; phenotype